In Memoriam Francisco Munguía Villalta (1976- 2020) The art of being with people - Collado Chaves, Adriana (2021)
Francisco Munguía Villalta (1976-2020) was a talented, highly productive and multifaceted Costa Rican artist. He produced a vast work, in different formats and techniques. He believed in the transforming power of art and consequently produced a socially committed work guided by the conviction that art should be accessible, inclusive, participatory and educational. He developed a plastic language anchored in his vocation of graphic humor. This, together with his fondness for social volunteering and community work, allowed him to establish easy links of communication and an extraordinary familiarity with people. Its iconographic universe of comic strip and its narrative full of parody and satire lives in his stickers, ceramics and paintings. His mural works managed not only to change the urban landscape, but also to reaffirm a sense of community, since his participatory methodology aspired to restore the power of people and to enable them to take over their own public spaces. Without delving into a chronological review of the artist’s journey, nor a logical analysis of his extensive production, this document shares an overview of aspects that are considered emblematic in the work of Munguía Villalta. This is a tribute to his memory and a celebration of the vitality of his extraordinary plastic legacy.